John Scottus Eriugena, a Christian philosopher - Wohlman, Avital (American catholic philosophical quarterly, 2005)
Most commentators find Eriugena's "On the division of nature" to be a variation on the theme of emanation, which flows from the One and back to it, bypassing concrete reality. My intention is to highlight the Christian traits of the four divisions of nature as the spiritual itinerary destined to lay bare the ontology of Augustine's "saeculum". Following Augustine, Eriguena identifies true philosophy with true religion. The central value of concrete reality, the third division of nature, is rooted in the mystery of the Incarnation. Reason's conclusions and rules of true religion prepare man to envisage the "aporia" of freedom of will as the "euporia" revealed by grace.